Coronary Sinus Diameter to Inferior Vena Cava Diameter Ratio in the Diagnosis of Cardiac Tamponade: A Novel Approach. Issue 4 (July 2020) - Ozcan Cetin, Elif Hande; Cetin, Mehmet Serkan; Könte, Hasan Can; Tak, Bahar Tekin; Ekizler, Firdevs Aysenur; Ozcan, Fırat; Cay, Serkan; Ozeke, Ozcan; Akcay, Burak; Topaloglu, Serkan; Aras, Dursun
Abstract : Background: In cardiac tamponade, coronary sinus (CS) as an intrapericardial structure can be easily compressed, whereas inferior vena cava (IVC) dilates. This inverse relationship may augment their roles in the evaluation of tamponade imaging. Aim: We assessed the usefulness of computerized tomographic measures of CS diameter and also CS/IVC ratio to predict tamponade in clinically stable patients with large pericardial effusion. Methods: Sixty-six clinically stable patients who had large pericardial effusions were included. Coronary sinus diameter was measured from the point at 1 cm proximal to the CS ostium. Inferior vena cava diameter was measured from the segment between its right atrial orifice and hepatic vein. Results: Patients with tamponade had smaller CS diameter and CS/IVC ratio. After adjusting with other parameters, only either CS diameter or CS/IVC ratio predicted tamponade, respectively. (Nagelkerke r 2 value for CS was 53.7% and 72.1% for CS/IVC ratio). In Receiver Operating Characteristic Curve analysis, a cutoff value of 6.85 mm for CS diameter had 82.6% sensitivity and 83.7% specificity and a cutoff value of 27% for CS/IVC ratio had 87.0% sensitivity and 86.0% specificity for predicting cardiac tamponade. Conclusions: The tomographic measures of both the CS diameter and the CS/IVC ratio predicted tamponade in clinically stable patients with large pericardial effusion. Compared with CS diameter, CS/IVC ratio seemed to be a more powerful predictor of tamponade.